Morphological abnormalities in the Striped panray, Zanobatus schoenleinii (Zanobatidae) from the coast of Senegal (Eastern Tropical Atlantic) - Capapé , Christian; Rafrafi-Nouira, Sihem; Diatta, Youssouph; Diaby, Almamy; Reynaud, Christian (Revista de Biología Marina y Oceanografía, 2022)
The capture of four abnormal specimens of the Striped panray, Zanobatus schoenleiniii was reported from shallow coastal waters surrounding the touristic area of Dakar, Republic of Senegal, and among them, some specimens displaying morphological deformities. A specimen exhibited a pectoral non-adherent to the head, a second was tailless, and two specimens displayed scoliosis at level of trunchal vertebrae and tail. The abnormalities are described and their causes and consequences herein considered.